Thursday

April 17, 2014

April 17, 2014

Number of results: 41,128

**math**

the expression 1/12 / (1/4 + 5/12) is equivalent to a - 1/18 b - 7/12 c - 1/8 d - 1/2 1/4= 3/12 3/12 + 5/12= 8/12 1/12 / 8/12 = 1/12 x 12/8 12/96=1/8 c-1/8
*Thursday, August 26, 2010 at 1:22pm by anonymous*

**investments**

Assume the following daily closing for the Dow Jones Industrial Average: Day DJIA Day DJIA 1 12,010 7 12,220 2 12,100 8 12,130 3 12,165 9 12,250 4 12,080 10 12,315 5 12,070 11 12,240 6 12,150 12 12,310 a.
*Wednesday, July 11, 2007 at 9:11pm by lia82*

**Applied Business Math/Colleg student**

(2/3)=(2*4)(3*4)=(8/12) (1/6)=(2*1)/(2*6)=(2/12) 2/3+1/6+11/12= =(8/12)+(2/12)+(11/12) =(21/12) =(12+9)/12 =(12/12)+(9/12) =1+(3*3)/(3*4) = 1 3/4 =(4/4)+(3/4) =7/4
*Saturday, January 29, 2011 at 8:19pm by Bosnian*

**Math**

5-x over 3 minus x-2 over 4 = 5/12 Is this what you meant? (5-x/3)-(x-2/4)=5/12 Multiply everything by 12. 12(5-x/3)-12(x-2/4)=12(5/12) remove parentheses 20-4x-3x+6=5 combine terms 26-7x=5 -7x=5-26 -7x=-21 multiply by -1 7x=21 divide both sides by 7 7x/7 = 21/7 x=3 CHECK IT...
*Friday, April 30, 2010 at 7:33pm by DrBob222*

**algebra**

First, find the common denominator of 3, 4, and 2. 5 1/3 = 5 4/12 2 1/4 = 2 3/12 3 1/2 = 3 6/12 Then add the whole numbers and the numerators. 5 4/12 + 2 3/12 + 3 6/12 = 10 13/12 = 11 1/12
*Sunday, December 27, 2009 at 7:43pm by Ms. Sue*

**maths**

12 - 1/9 / (4/3) + (1/2)^2 = 12 - 1/9 * 3/4 + 1/4 = 12 - 3/36 + 1/4 = 12/1 - 1/12 + 1/4 = 144/12 - 1/12 + 3/12 = 146/12 = 12 2/12 = 12 1/6.
*Wednesday, August 3, 2011 at 9:09am by Henry*

**calculus hw**

(0 - (1/4 - 1 + 1/3) note plus 1/3 1 -1/4 -1/3 12/12 -3/12 - 4/12 5/12 then 5/12 +8/3 5/12 + 32/12 37/12
*Sunday, December 15, 2013 at 2:08pm by Damon*

**Math**

Use 2 y for x in the second equation 4 *(2 y) + y = 12 8 y + y = 12 9 y = 12 y = 12/9 y = 4/3 then go back and get x from x = 2 y x = 2 y x = 8/3 then check x = 2*4/3 = 8/3 yes 4(8/3) + 4/3 = 12 ? 32/3 + 4/3 = 12? 36/2 = 12? 12 = 12 ? yes, check
*Wednesday, December 24, 2008 at 2:18am by Damon*

**math**

not clear what 12/8/4 means is it (12/8)÷4 or is it 12÷(12/8) ? first: (12/8)÷4 = (3/2)÷4 = (3/2)x(1/4) = 3/8 second: 12÷(12/8) = 12÷(3/2) = 12x(2/3) = 8
*Monday, October 12, 2009 at 7:16pm by Reiny*

**math**

2 1/4 + 3/4 + 1/3 2 3/12 + 9/12 + 4/12 27/12 + 9/12 + 4/12 = 40/12 = 3 4/12 = 3 1/3 Or the easier way: 5 - 1 2/3 = 3 1/3
*Thursday, November 10, 2011 at 8:36pm by Ms. Sue*

**Math**

we start knowing nothing: x x x x x x x x x x x x median=12 (average of 2 center values) x x x x x 12 12 x x x x x mode=7. we have 2 12's, so let's have 3 7's: x x 7 7 7 12 12 x x x x x max is 18: x x 7 7 7 12 12 x x x x 18 range is 13, so min=5 5 x 7 7 7 12 12 x x x x 18 fill...
*Thursday, October 10, 2013 at 9:19pm by Steve*

**math**

You need a common denominator to add fractions. 12 is the smallest number divisible by 4 and 6. 3/4 = 9/12 2/6 = 4/12 9/12 + 4/12 = 13/12 = 1 1/12
*Tuesday, April 12, 2011 at 6:57pm by Ms. Sue*

**Math**

12 - 3 = 9 pieces they didn't eat 9/12 Divide the numerator and the denominator by 3 9/12 = 3/4 Another way to figure it out is subtract 12/12 - 3/12 = 9/12 = 3/4
*Monday, February 13, 2012 at 5:22pm by Ms. Sue*

**Math**

First we have to find equivalent fractions with the same denominator. 2/3 = 8/12 1/6 = 2/12 Now add the numerators. 8/12 + 2/12 + 11/12 = 21/12 = 1 9/12 = 1 3/4
*Wednesday, July 24, 2013 at 9:10pm by Ms. Sue*

**algebra**

make everything into twelfths, so you have... 9/12k-2/12 =6/12 take out the 2/12 so... 9/12k=8/12 so now you divide 8/12 by 9/12 = 8/12*12/9 = 96/108 and simplify to 8/9 so k = 8/9
*Tuesday, October 6, 2009 at 9:50pm by brandon*

**Maths**

a+d = ar a = 12 r < 1 3/2 (2a+2d) = a(1+r+r^2) - 4/3 3ar = a(1+r+r^2) - 4/3 36r = 12(1+r+r^2) - 4/3 r = 2/3 or 4/3 r=2/3: 12+d = 12* 2/3 d = -4 AP = 12 8 4 0 ... GP = 12 8 16/3 32/9 ... check 12+8+4 = 12+8+16/3 - 4/3 YES
*Sunday, February 3, 2013 at 4:35pm by Steve*

**math**

simplify 12b^-6/3a^0 you should read my notes on "rob"'s questions if you're not the same person. lol if that's 12(b^-6), then the answer is 12/(b^6) if that's (12b)^-6, then the answer is 1/((12^6)*(b^6)) 12b^-6/3a^0. I think this is 12(b^-6)/3(a^0). a^0 = 1; therefore, 12(b...
*Tuesday, October 10, 2006 at 11:09pm by jim*

**6th grade Math**

sum = 1 8/12 + 2 9/12 + 3 4/12 + 1 8/12 + 2 9/12 sum = 9 + 38/12 = 9 + 3 2/12 = 12 1/6 av = (12 1/6) / 5 av = 2 2/30 = 2 13/30 part 2 x = 15 - 12 1/6 x = 14 6/6 - 12 1/6 x = 2 5/6
*Wednesday, January 7, 2009 at 8:37pm by Damon*

**geometry**

12^2 = 12 * 12 = 12 + 12... + 12 = (2*12) + (2*12)... + (2*12) That should give you a start.
*Tuesday, May 17, 2011 at 3:59pm by PsyDAG*

**Calculus**

write it as y = 3(x^2 + 12)^-1 y' = -3(x^2 + 12)^-2 (2x) = -6x(x^2 + 12)^-2 y'' = (-6x)(-2)(x^2 + 12)^-3 (2x) - 6(x^2 + 12)^-2 = 24x^2 (x^2+12)^-3 - 6(x^2+12)^-2 = 6(x^2+12)^-3 [ 4x^2 - x^2 - 12] = 6(x^2+12)^-3 [ 3x^2 -12] = 18(x^2 -4)/(x^2 + 12)^3 or 18(x^2-4)/(x^2 + 12)^3
*Thursday, December 15, 2011 at 1:12am by Reiny*

**Math**

(x-p)(x-q) = x^2 + b x + 12 p q = 12 b = +/-(p+q) p and q must be the same sign and product 12 so 1) p = 1, q = 12 2) p = 3, q = 4 3) p = -1 , q = -12 4) p = -3, q = -4 so b = 13 b = -13 b = 7 b = -7 try those x^2 + 13 x + 12 = (x+12)(x+1) x^2 - 13 x + 12 = (x-12)(x-1) x^2 + 7...
*Thursday, January 30, 2014 at 4:17pm by Damon*

**Algebra/Number Theory**

The numbers are 12, 12+d, 12+2d, 452 12, 12+d, (12+d)r, (12+d)r^2=452 (12+d)r^2 = 452 12+2d = (12+d)r so, r = (12+2d)/(12+d) (12+d)((12+2d)/(12+d))^2 = 452 (12+2d)^2 = 452(12+d) d = 112.71 r = 1.09377 The numbers are 12, 124.71, 237.42, 452
*Tuesday, July 23, 2013 at 1:29pm by Steve*

**Math**

the first part is just 3/12 + 4/12 + 2/2 = 3/12 + 4/12 + 12/12= 19/12 of the school. The second part is 19/12 - 3/12 = 16/12
*Tuesday, October 23, 2012 at 6:55pm by Sam*

**math**

Take number 12 and subtract summ of first numbers 2 * 6 = 4 become 12 - ( 2 + 6 ) = 12 - 8 = 4 4 * 1 = 7 become 12 - ( 4 + 1 ) = 12 - 5 = 7 8 * 3 = 1 become 12 - ( 8 + 3 ) = 12 - 11 = 1 So 5 * 5 = x become 12 - ( 5 + 5 ) = 12 - 10 = 2 x = 2 5 * 5 = 2
*Monday, August 20, 2012 at 5:50am by Bosnian*

**math**

I would change it to base 10, do the multiplication , then convert back to base 12 1B7 = 12^2 + 1(12) + 7 = 286 29 = 2(12) + 9 = 33 289*33 = 9537 9537 = 5(12)^3 + 897 = 5(12)^3 + 6(12)^2 + 33 = 5(12)^3 + 6(12)^2 + 2(12) + 9 = 562912
*Wednesday, November 11, 2009 at 3:17pm by Reiny*

**algebra**

P = Perimeter P = a + b + c a = P / 3 b = P / 4 P = a + b + c = P / 3 + P / 4 + 7 P / 3 = 4 P / 12 P / 4 = 3 P / 12 P = P / 3 + P / 4 + 7 P = 4 P / 12 + 3 P / 12 + 7 P = 7 P / 12 + 7 P - 7 P / 12 = 7 12 P / 12 - 7 P / 12 = 7 5 P / 12 = 7 Multiply both sides with 12 5 P = 7 * ...
*Thursday, December 8, 2011 at 4:54am by Anonymous*

**math**

12/12 - (3/12 + 2/12) 12/12 - 5/12 = 7/12 therefore there are 7 green marbles
*Wednesday, January 22, 2014 at 9:46pm by Anon*

**fractions**

First we need to find the common denominator and add the fractions. Since, 12, 6, and 3 all go evenly into 12, that's the common denominator. 1/6 = 2/12 1/3 = 4/12 2/12 + 4/12 + 3/12 = 9/12 That can be simplified. 9/12 = 3/4 4/4 - 3/4 = 1/4 not colored
*Tuesday, February 26, 2013 at 6:21pm by Ms. Sue*

**Math/Fractions**

First we need to find the common denominator and add the fractions. Since, 12, 6, and 3 all go evenly into 12, that's the common denominator. 1/6 = 2/12 1/3 = 4/12 2/12 + 4/12 + 3/12 = 9/12 That can be simplified. 9/12 = 3/4 4/4 - 3/4 = 1/4 not colored
*Tuesday, February 26, 2013 at 6:21pm by Santeria*

**Math**

name for 12 in mathematical terms: 6+6=12 9+3=12 5+7=12 3*4=12 12-0=12 ect.
*Sunday, March 13, 2011 at 2:31pm by Anonymous*

**algebra**

list the factors of 12, 2 * 6 3 * 4 12 * 1 Now, when added, must equal 8 2 * 6 = 8 3 * 4 = 7 12 * 1 = 12 so, since 2 * 6 = 12 and 2 + 6 = 8 x^2+8x+12 (x + 2)(x + 6)
*Wednesday, January 12, 2011 at 11:50am by helper*

**Advanced Functions**

if cosx = 5/13, (recognize the 5,12,13 triangle ?) sinx = 12/13 tanx = 12/5 if cosy = -5/13 and y is in III siny = -12/13 tany = 12/5 2sinx+2siny+2cosx-2tanx+tany+2cosy = 2(12/13) + 2(-12/13) + 2(5/13) -2(12/5) + (12/5) + 2(-5/13) = - 12/5 or -2.4
*Tuesday, November 19, 2013 at 8:12pm by Reiny*

**Algebra 2**

Write an equation for the nth term of the geometric sequence: -12,4,-4/3 I had a_n=-12(3)^(n-1) but that is not a choice on the multiple answers they have = -12(1/3)^(n-1) = 12(-1/3)^(n-1) = -12(-1/3)^(-n+1) = -12 (-1/3)^(n-1)
*Saturday, November 17, 2007 at 8:07pm by Chelsey*

**AIG 4th Grade Math**

Let x = total players 1/2 x + 1/6 x + 1/6 x + 1/12 x = x - 2 Get common denominator. 6/12 x + 2/12 x + 2/12 x + 1/12 x = x - 2 Add like terms. 11/12 x = x - 2 Multiply both sides by 12. 11x = 12x - 24 You should be able to take it from there. I hope this helps.
*Tuesday, January 19, 2010 at 8:56pm by PsyDAG*

**math**

solve and express the answer as an improper fraction in lowest terms 5/6-2/3(6-1/2)+3/4 I did 5/6-4+1/3+3/4 -31/6+1/3+3/4 -19/6+1/3+3/4 -38/12+4/12+9/12 -34/12+9/12 -25/12 is this correct? thanks
*Sunday, January 20, 2013 at 7:21pm by b6*

**MaTh fractions add subtract**

#12, what happened to the y ? check your typing of #12, is the second supposed to be a mixed fraction? 16. -1 2/3 - 2 1/4 = -5/3 - 9/4 = -20/12 - 27/12 = - 47/12 or -3 11/12
*Wednesday, December 21, 2011 at 6:08pm by Reiny*

**MATH HELP!!**

1/6 = 2/12 2/8 = 1/4 = 3/12 2/12 + 3/12 = 5/12 12/12 - 5/12 = 7/12 You're right.
*Monday, December 6, 2010 at 9:59pm by Ms. Sue*

**Calculus**

what's the problem? (k,2k-1,3)•(k,5,-4) = k*k + (2k-1)(5) + 3(-4) so, we need k^2 + 10k - 5 - 12 = 7 k^2 + 10k - 24 = 0 (k-2)(k+12) = 0 so, k=2 or -12 k=2: (2,3,3)•(2,5,-4) = 4+15-12 = 7 k=-12: (-12,-25,3)•(-12,5,-4) = 144-125-12 = 7
*Thursday, March 29, 2012 at 8:23pm by Steve*

**Math :(**

1/4 = 3/12 2/3 = 8/12 3/12 + 8/12 = 11/12 24/12 - 11/12 = 13/12 = 1 1/12
*Thursday, October 27, 2011 at 8:10pm by Ms. Sue*

**math**

You can add up fraction of yellow and blue subtract from 1 to get green 1- ([2/12+ 3/12) 1- 5/12 (12-5)/12 = 7/12 Green is 7/12
*Monday, October 28, 2013 at 5:11pm by Kuai*

**math**

4 6/9 + 3 7/12= You need a common denominator. 4 6/9 = 4 2/3 = 4 8/12 4 8/12 + 3 7/12 = 7 15/12 = 8 3/12 = 8 1/4
*Tuesday, February 23, 2010 at 10:36pm by Ms. Sue*

**math word problem**

You're welome. x - 3/4 + 1/6 = 17/12 x - 9/12 + 2/12 = 17/12 x - 7/12 = 17/12 x = 17/12 + 7/12 x = 24/12 x = 2
*Thursday, October 21, 2010 at 10:11pm by Ms. Sue*

**Algebra I**

(time t, blocks d) (0 , 12) (6 , 8 ) d is distance from house in blocks d = m t + b 12 = 0 + b so b = 12 8 = m *6 + 12 -4/6 = m m = -2/3 so d = -(2/3) t + 12 0 = -(2/3) t + 12 t = (3/2) * 12 = 18 minutes
*Wednesday, January 7, 2009 at 7:46pm by Damon*

**explorations in math**

So it is now in base 12 ?? powers of 12: 12, 144, 1728, ... 206812 = 2(12^3) +0(12^2) + 6(12) + 8 = 3456 + 0 + 72 + 8 = 353610
*Sunday, May 15, 2011 at 9:04pm by Reiny*

**algebra 1**

11/12-(1/3+1/4) = 11/12 - 1/3 - 1/4 = get a common denominator which is 12. 11/12 - 4/12 - 3/12 = Add the numerators to obtain 11-4-3 = 4 so the answer is 4/12 which reduces to 1/3 Check my work.
*Tuesday, July 15, 2008 at 8:04pm by DrBob 222*

**physics**

a. I = E/R = 12/0.05 = 240A. 0.95I = 0.95*240 = 228A. Vr + Vc = 12 228*0.05 + 12/e^(t/T) = 12 11.4 + 12/e^(t/T) = 12 12/e^(t/T) = 12-11.4 = 0.6 e^(t/T) = 12/0.6 = 20 t/T = 3. T = L/R = 0.09/0.05 = 1.8=Time constant. t/1.8 = 3 t = 5.4 s. b. Energy = 0.5L*I^2=.5*0.09*(228)^2 = ...
*Friday, April 12, 2013 at 12:11am by Henry *

**math**

(2x+1)^12 = 2^12 x^12 + 12*2^11 x^11 + ... (x+1)^18 = x^18 + 18x^17 + ... multiply the two expansions to get 2^12 x^30 + (18*2^12 + 12*2^11) x^29 + ... so, we have 18*2^12 + 12*2^11 = 98304
*Monday, March 18, 2013 at 12:32pm by Steve*

**Math**

A line-up has 9 members, of which the first three have been determined. Therefore it is out of 12 remaining we choose 6. The number of ways is C(12,6), or 12 choose 6. The formula for "n choose r", or C(n,r) is C(n,r)=n!/(r!(n-r)!) So "12 choose 6" = 12!/(6!(12-6)!) = 12*11*10...
*Sunday, April 17, 2011 at 4:47pm by MathMate*

**math question**

First find a common denominator= 12 3/4= 9/12 and 1/3= 4/12 then add= 9+4= 13 = 13/12 then change to a mixed # = 1 1/12 1 is a whole and then 1/12 hope this helps :)
*Monday, November 26, 2012 at 7:53pm by Rylee*

**explorations in math**

For 206812 converted to base 10, you would do the following sum: 2*12^3+ 0*12^2+ 6*12^1+ 8*12^0 =2*1728 + 0*144 + 6*12 + 8*1 = ?
*Sunday, May 15, 2011 at 9:04pm by MathMate*

**math**

i need help on a proof, can anyone help? please HELP!!!! me on the difference between 3/4 and 1/3???????? You have to find the common denominator of 3 and 4, which can be 12. The first fraction becomes 9/12 and the second becomes 4/12. 9/12 - 4/12 = 5/12.
*Tuesday, January 2, 2007 at 6:34pm by nicole*

**math**

36 hrs, 12 minutes <---> 1 day + 12 hrs , 12 min 6:12 pm + 12:12 = 6:24 am (wouldn't it be nice it time was metric ??)
*Wednesday, February 26, 2014 at 8:54pm by Reiny*

**math**

from your correct 5/6-4+1/3+3/4 I would have done as follows, since LCD = 12 = 10/12 - 48/12 + 4/12 + 9/12 = -25/12 all done, you were correct
*Sunday, January 20, 2013 at 7:21pm by Reiny*

**math fractions**

a 4th grader? compare the fractions. All can be written as 12ths. 3/12; 2/12 (which is 1/6); and 4/12 (which is 1/3). now put them in order... 2/12, 3/12, 4/ 12
*Tuesday, February 26, 2013 at 4:49pm by bobpursley*

**Math**

I am not sure that I answered this question right. A) 3/4 / -12= 3/4 / -11 12/12= 3/4 / - 144/12= 9/12 / -144/12= 9/12 * -12/144= -9/144=-16. B) 5/4 / 2 2/3= 15/12 / 32/12= 15/12 * 12/32= 15/32. Is this correct? Thanks
*Monday, July 6, 2009 at 11:02pm by B.B.*

**Geometry**

Any side of a triangle must be positive: 12-x>0 x<12 The sum of any two sides must be greater than the third. In this case, 12-x + 12 > 12+x => 24-x > 12 + x => x < 6 Also, 12+12+x > 12-x 2x>-12 x>-6 Therefore the conditions are that -6<x<6
*Thursday, March 1, 2012 at 9:11pm by MathMate*

**Please help!**

f(x-12) shifts the graph right by 12 units. (Now all the x-coordinates are 12 less than they were...) g(x) = f(x-12) = ((x-12)+10)^2 = (x-2)^2
*Sunday, March 16, 2014 at 11:12pm by Steve*

**pre-calc**

(x-3)^(1/2) - 3(x+12)^1/2 = -11 x-3 = [-11 + 3(x+12)^1/2]^2 x-3 = 121 -66 + 9(x+12)^2 + 9(x+12) x = 58 + 9(x+12)^2 + 9(x+12) That can be reduced to a quadratic and solved for x
*Friday, November 9, 2007 at 7:05pm by drwls*

**Math Fractions**

12/12 = 1. To divide 1 by a fraction, turn the fraction upside down. 1/(3/8) = 8/3 Or do this: 12/12 / (3/8) = 12/12 x (8/3) = 96/36 = 8/3
*Thursday, January 5, 2012 at 11:48pm by drwls*

**Math**

Can you make a capital i on your computer? It may have something to do with factors of 12 but it may be coincidental that 1/12 + 1/12 = 2/12 = 1/6 so we know 2 is a factor of 12.
*Tuesday, September 29, 2009 at 10:06pm by DrBob222*

**MAth**

8/12, 17/12, 26/12, 35/12 _, _, _ ah ha, each is 9/12 bigger than the one before it
*Wednesday, January 20, 2010 at 8:02pm by Damon*

**MEASUREMENT**

If the perimeter of a square is 12 inches wouldn't you just add 12+12+12+12 and get 48?
*Friday, August 28, 2009 at 11:58pm by ggift*

**math**

1/3 x = 5/12 Divide both sides of the equation by 1/3 x = 5/12 divided by 1/3 x = 5/12 * 3/1 x = 15/12 = 1 3/12 = 1 1/4
*Sunday, January 24, 2010 at 8:21pm by Ms. Sue*

**math**

From x/3+2=x/6 multiply both sides by the LCM of the denominator, namely 6: 6(x/3)+6*2 = 6(x/6) 2x + 12 = x x +12 -12 = -12 x=-12
*Friday, August 27, 2010 at 2:57pm by MathMate*

**Math**

Which of the flowing formulas a correct rewriting of the formula a=6b - 12? A. b= a- 12/6 B. b= a + 12/6 C. b= a/6 + 12 D. b= 6a - 12
*Wednesday, April 13, 2011 at 8:46pm by Leah*

**Intermediate Algebra 137**

The LCD of your three fractions is 12 So let's multiply each term by 12 12(x/2) + 12(x/3) = 12(3/4) 6x + 4x = 9 10x = 9 x = 9/10
*Saturday, June 8, 2013 at 6:04pm by Reiny*

**math subtracting mixed numbers**

First, let's find the common denominator and the equivalent fractions. 9 3/4 = 9 9/12 4 1/3 = 4 4/12 Subtract: 9 9/12 - 4 4/12 = 5 5/12
*Sunday, September 29, 2013 at 9:11pm by Ms. Sue*

**Math 7th grade**

6 11/12=6+(11/12) 6*12=72 , 6=(72/12) 6+(11/12)=(72+11)/12= (83/12) 4 5/12=4+5/12 4*12=48 , 4=(48/12) 4+5/12=(48+5)/12= (53/12) 6 11/12-4 5/12=(83/12)-(53/12)=(30/12)= (5*6)/(2*6)=5/2
*Sunday, October 17, 2010 at 9:09pm by Bosnian*

**statistics**

Your first 3 questions deal with binomial distribution in probability. A) for exactly 10 out of 12 C(12,10) (.6)^10 (.4)^2 = 66(.00605)(.16) = .0639 B) repeat the same calculations as above for 10 out of 12 + 11 out of 12 + 12 out of 12 C)that would be C(12,12)(.6)^12 = ....
*Saturday, January 2, 2010 at 10:13am by Reiny*

**arithmetic**

3g = 6b = 4w factor each to find least common multiple 3 = 3 6 = 3*2 4 = 2*2 so we need 2*2*3 = 12 12/3 = 4 12/6 = 2 12/4 = 3 so 4 green 2 blue 3 white for 12 of each
*Wednesday, December 1, 2010 at 4:32pm by Damon*

**Math PLEASE HLP!!!!**

use fraction bars to help: a) 11/12=w+y b)3/8=3/6-k c)1/4=n-7/12 d) how many 1/12's are in 1 1/4? help! im sooooooo..... confused! for d) put 1 1/4 into an improper fraction. That would be 5/4. Follow so far? Then cross multiply 5/4 and x/12. So, 4x = 5(12). from here just ...
*Tuesday, January 2, 2007 at 8:16pm by Destiny*

**Algebra Absolute Value**

|-2/3(x-6)| = 12 expand the inside |(-2/3)x + 4| = 12 so (-2/3)x + 4 = 12 or (2/3)x - 4 = 12 (-2/3)x = 8 OR (2/3)x = 16 x = -12 OR x = 24
*Saturday, October 27, 2007 at 10:39pm by Reiny*

**math**

5 3/4=5+(3/4)=5+(9/12)=(60/12)+(9/12)=69/12 2 5/6=2+5/6=2+(10/12)=(24/12)+(10/12)=34/12 (69/12)-(34/12)= 35/12=(24/12)+(11/12) =2+(11/12)= 2 11/12
*Wednesday, October 20, 2010 at 11:13pm by Bosnian*

**math**

y/12 - 2/3 = 1/4 y/12 = 1/4 + 2/3 y/12 = 3/12 + 8/12 y/12 = 11/12 y = ?
*Tuesday, September 21, 2010 at 9:06pm by Ms. Sue*

**Math Stil don't know how to do this problem :(**

15 1/6 - 6 5/12. Change the mixed numbers to improper fractions by multiplying the whole numbers by the denominator of the fraction and adding the numerator: 91/6 - 77/12, Find the common denominator(=>12). In this case, it is = to 12; because 6 will divide into 12 with no ...
*Sunday, October 17, 2010 at 9:45pm by Henry*

**Math Stil don't know how to do this problem :(**

You could turn them both into improper fraction. 15 1/6 would now be 91/6. Then 6 5/12 would be 77/12. 6 and 12 common denominator is 12 so 91/6=182/12. 77/12 = 77/12. 182/12- 77/12= 105/12. Then you turn 105/12 into a mixed number which would be 8 9/12= 8 3/4.
*Sunday, October 17, 2010 at 9:45pm by Shadow*

**math**

The pizza is 12/12, meaning it has 12 total slices. If 5 people each had 2 slices (this is what 2/12 means) then: 5* (2/12)= 0.83= 10/12 10/12 is how much pizza was eaten. To figure out how much is left, subtract how much was eaten from the total. (12/12)- (10/12)= 2/12
*Monday, March 24, 2014 at 4:04pm by Elle*

**math**

Do what is in parenthesis first. You get 12 + {12 - 36/4} Next do what is in the brackets 12 - 36/4 = 48/4 - 36/4 = 12/4 = 3 or 12 - 9 = 3 whichever way you prefer. Then, you are left with 12 - 3 Hope this makes sense!
*Thursday, April 9, 2009 at 12:59pm by MsPJ*

**Binomial Probability**

Prob(male) = .7 prob(female) = .3 a) prob(6 are male_ = C(12,6) (.7)^6 (.3)^6 = .07925 b) prob(6 or more are female) = prob(6 F) + prob(7 F) + prob(8 F + .. prob(12 F_ = C(12,6)(.3)^6 (.7)^6 + C(12,7) (.3)^7 (.7)^5 + ... + C(12,12) (.3)^12 (.7)^0 I will let you do the button ...
*Saturday, November 10, 2012 at 4:32pm by Reiny*

**8th grade**

n+3=12 12 - 3 _____ 9 n+3=12 CHECK IT! 9+3=12 9 n=9 +3 ___ 12 TADA!!!
*Wednesday, May 27, 2009 at 5:06pm by krys*

**math**

y =kx , where k is a constant given: x=5 , when y = 12 12 = 5k k = 12/5 so y = (12/5)x when x = 7.5 y = (12/5)(7.5) = 18
*Sunday, February 17, 2013 at 2:21pm by Reiny*

**math**

12. _ _ 12.27 12.45 12.63 12.81
*Monday, March 4, 2013 at 4:47pm by Ms. Sue*

**Math**

The common denominator is 12 2 1/4 = 2 3/12 2 1/4 = 2 3/12 1 1/2 = 1 6/12 2 1/6 = 2 2/12 Add them together.
*Monday, April 29, 2013 at 8:40pm by Ms. Sue*

**Math**

You need to convert all the denominators into 12: 1/2 = 6/12 1/4 = 3/12 1/3 = 4/12 1/6 = 2/12
*Sunday, October 27, 2013 at 11:26pm by Anonymous*

**Alg 2**

(1 + 2^1/6 - 2^1/12)^-1 1/(1 + 2^1/6 - 2^1/12) 1/[(2^11/12 + 2^1/12 - 1)(2^1/12)] That can be factored somewhat, but it won't get any simpler than what you started with.
*Saturday, February 8, 2014 at 11:13pm by Steve*

**Pre-algebra**

An equation is a statement of equality containing one or more variables. To solve an equation means, find the value of the variable for which the equation satisfy An example of an equation is x + 5 12. Solution: x + 5 = 12 x = 12 - 5 x = 7 7 is a solution of the equation x + 5...
*Saturday, May 21, 2011 at 1:01pm by clarissa*

**math**

8/3 = 32/12 3/4 = 9/12 32/12 - 9/12 = 23/12 = 1 11/12 pound left
*Wednesday, November 14, 2012 at 5:17pm by Ms. Sue*

**5th grade**

8 1/4 - 4 5/6 First find the common denominator and change the fractions to equivalent fractions. 8 1/4 = 8 3/12 4 5/6 = 4 10/12 Then add: 8 3/12 + 4 10/12 = 12 13/12 = 13 1/12
*Sunday, January 3, 2010 at 5:23pm by Ms. Sue*

**Algebra I**

the two ordered pairs from your information are (0,12) and (6,8) slope = (12-8)/-6 = -2/3 So Blocks = (-2/3)t + b using (0,12) 12 = 0 = b b = 12 so the linear equation is Blocks = (-2/3)Time + 12 when he reaches Sharon's house Blocks = 0 so 0 = (-2/3)time + 12 (2/3)time = 12 ...
*Wednesday, January 7, 2009 at 7:46pm by Reiny*

**algebra & trigonometry**

x(2x+5)=12 2x^2+5x-12=0 (x+4)(2x-3)=0 2x-3=0 2x=3 x=3/2 3/2(2(3/2)+5)=12 3/2(3+5)=12 3/2(8)=12 24/2=12 12=12 width=3/2 length=8
*Tuesday, February 11, 2014 at 7:46pm by daniel*

**math**

To compare fractions, you need to use common denominators. 5/6 = 10/12 10/12 = 10/12 4/6 = 8/12 Which is larger -- 6/12 or 8/12?
*Tuesday, April 5, 2011 at 8:02pm by Ms. Sue*

**math**

area of sides = 2 L *6 + 2 W*6 = 12 L + 12 W area of bottom = L W total area = L W + 12 L + 12 W = 480-4*36 so L W + 12 L + 12 W = 336 but L = W + 4 (W+4)W + 12(W+4) + 12 W - 336 = 0 W^2 + 28 W -288 = 0 (W -16)(W+18) = 0 W = 16 L = 16+4 = 20
*Saturday, April 21, 2012 at 6:05pm by Damon*

**math - fractions**

First, let's find the common denominators and add the fractions. 2 1/3 = 2 4/12 1 1/4 = 1 3/12 1 5/12 = 1 5/12 ________________ . . . . 4 12/12 = 5 Subtract 5 from 8 to find the amount of jojoba oil Mara used.
*Thursday, September 13, 2007 at 3:50pm by Ms. Sue*

**integrated algebra**

1.set common denominator: x(x-12) 2. multiply (x-12) (x+1) = -7 (x) _______________________________ (x-12) x = (x-12) (x) 3. multiply out numerator: x2 -11x-12 = - 7x x2 -4x-12 = 0 (x+2) (x-6) =0 x = -2 or x =6
*Monday, March 29, 2010 at 3:40pm by John Jacobs*

**geometry**

variable L= length and we have 12:2 is = 6 and then the ratio 2/3 is 2/3 L=9 check: 12-9=3 If they asking continues answer will be 3 so both sides are make sense 6=2/3(9) check from the 12 feet long we have 12= L+3= 12=12 if this helpful 6= 6
*Sunday, February 27, 2011 at 6:49pm by Nhi giap*

**math/ elimination& substitution**

well, since one equation says y=... I'd use substitution. 2x - 3(-x + 7/12) = -1/12 2x + 3x - 21/12 = -1/12 5x = 20/12 x = 4/12 = 1/3 using elimination, rearrange things a bit first to get 2x-3y = -1/12 x+y= 7/12 2x-3y = -1/12 3x+3y = 21/12 add to get 5x = 20/12 x = 4/12 = 1/3
*Thursday, May 16, 2013 at 4:20pm by Steve*

**math**

Yes, you subtract 12 from both sides to isolate x. x + 12 = 6 x + 12 - 12 = 6 - 12 x = -6
*Friday, November 30, 2007 at 5:03pm by Michael*

**Math**

your common denominator is -12 so 4/-3+(5/-12) = 16/-12 + 5/-12 = 21/-12 = - 7/4
*Saturday, September 26, 2009 at 9:36pm by Reiny*

**MATH**

2 3/4 + 1/12 = The common denominator is 12. 2 9/12 + 1/12 = 2 10/12 = 2 5/6
*Sunday, November 10, 2013 at 2:39pm by Ms. Sue*

**Math Subtracting mixed numbers**

3 3/4= 12/4 + 3/4= 15/4 1 1/3= 3/3 + 1/3= 4/3 15/4 - 4/3= (3*15)/(3*4) - (4*4)/(4*3) =45/12 - 16/12 =29/12 =2 5/12 OR 1 17/12
*Saturday, December 15, 2012 at 1:00pm by Elsi*

Pages: **1** | 2 | 3 | 4 | 5 | 6 | 7 | 8 | 9 | 10 | 11 | 12 | 13 | 14 | 15 | Next>>